Biopolimeric Nano Structural Compositions Based on Caramelized Honey - Кurta, S.А.; Khatsevich, О.М.; Tsap, М.R.; Ondrušová, D.; Gromovy, T.M.; Boyko, N.V. (Physics and Chemistry of Solid State, 2019)
The article deals with chemical properties of honey as well as wax and beeglue before and after the process of caramelization. The research has been done to study chemical reactions of caramelization of honey and other bee products; the biochemical properties of the obtained substances have been investigated as well. It has been revealed that biological activity of the compound after thermochemical heating of honey in the presence of special catalysts was discovered. Infrared spectra, moisture, viscosity, size and distribution of nanoparticles, elemental composition, oxymethylfurfural content, diastase number of caramelized honey have been investigated. The difference between the sizes of nanoparticles of raw and caramelized honey has been revealed, namely caramelized honey (1.5-2.0 times) of smaller size encourages their biochemical activity. On the basis of the results obtained from caramelized honey, wax and beeglue as well as their properties, the chewing gum with biologically active components for the prevention and treatment of periodontal tissue diseases (gingivitis, periodontitis and periodontal disease) was invented. Clinical studies on chewing gum with honey, wax, and beeglue have confirmed that it provides health benefits among 72 % of patients.